New design of high voltage surge arresters - Darus, Ahmad (Universiti Teknologi Malaysia, 2004)
Zinc-oxide material is an important and widely used element in the high voltage gapless surge arresters. Equally important is the usually polymeric insulating material used for the surge arrester housing. This work aims to develop a new design of gapless high voltage surge arrester using an improved zinc-oxide material and a new natural rubber based insulating material. The first part of this work deals with the development of a newly formulated thermoplastic elastomes (TPE) compound based on the linear low-density polyethylene (LLDPE) and natural rubber (NR) blends. The effects of alumina trihydrate (ATH) fillers on the TPE compound were also studied. The electrical tracking performance of the compound was investigated using a newly constructed surface tracking system based on incline-planned test method. The LLDPE and natural rubber blend was found to be reliable as an alternative high voltage insulating material. The second part of the work involves the development of a new test module suitable for transient response studies of zinc-oxide surge arresters. It companies of a high voltage transducer based on the D-dot probe principle and a coaxial high current transducer as well as the high current impulse generator. The module is suitable for testing arresters with voltage and current ratings at up to 100kV and 10kA respectively. Initial tests on distribution level zinc-oxide surge arresters provide some data for the development of a new equivalent circuit representation of the zinc-oxide surge arrester under fast transient condition and hence better characterization of its electrical behavior.